The absence of the mother and the assertion of the subjectivity in Carmen Laforet's "Nada" - Calmes, Victoria (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
In Carmen Laforet’s Nada the search for the assertion of the subjectivity is originated by a emptiness. The theme of the absence of the mother figure is a central idea in this novel. The pinning for the maternal in the social and economic circumstances of the Spanish postwar period has a repercussion on the image of the main character. Following different theories about maternity, my essay studies the essential importance of the mother figure from the earliest stages of the individual’s development and in the formation of his/her subjectivity.